THE ROLE OF HEREDITARY DISORDERS OF METABOLISM of FOLIC ACID IN THE DEVELOPMENT OF CONGENITAL DEFECT FETUS IN WOMEN WITH EPILEPSY AND RECEIVING ANTIEPILEPTIC DRUGS - D. V. Dmitrenko; N. A. Shnayder; Y. B. Govorina; A. V. Muravievа; K. A. Gazenkampf (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: the aim of our research was assessment of the cumulative risk of disorders of metabolism of folic acid in the development of the congenital defect fetus (CDF) in women with epilepsy and receiving antiepileptic drugs (AEDs). Materials and Methods: the study included 124 cases of pregnancy. Results: 54.7% of the daily doses of AEDs exceeded teratogenic levels; at 4.9% - registered the CDF. In 57.1% cases - the CDF associated with hereditary metabolic disorders of folic acid. Conclusions. Women which receive AEDs and have hereditary metabolic disorders of metabolism of folic acid are at increased risk group of developing congenital malformations.